2019
DOI: 10.1111/1748-5967.12397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with paste and sauce extract made using Tenebrio molitor larvae on ethanol‐damaged HepG2 cells

Abstract: In this study, we made koji using protein‐rich Tenebrio molitor larvae (TML) inoculated with Aspergillus oryzae, and then used the koji to prepare a paste and a sauce. The TML koji showed the highest amino nitrogen, protease activity, and free amino acids content when it was fermented for 72 h after inoculation with 0.8% A. oryzae. The koji was aged in 20% saltwater for 50 days, and then the paste and sauce were separated. To evaluate the effect of TML paste and sauce on ethanol (EtOH)‐damaged hepatocytes, asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…As the GSH enzyme in the liver plays a significant role in liver defense, protecting against liver damage by detoxifying many toxic compounds [ 40 ], we expected that the PBL paste and sauce might have a hepatoprotective role through antioxidant activity. This antioxidant effect is similar to that of the paste and sauce extracts made of 30% (TMP30: 151.07%, 151.75%; TMS30: 148.69%, 151.37%), 50% (TMP50: 150.31%, 156.69%; TMS50: 150.63%, 151.27%), and 100% (TMP100: 152.11%, 158.30%; TMS100: 151.74%, 151.91%) TML [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…As the GSH enzyme in the liver plays a significant role in liver defense, protecting against liver damage by detoxifying many toxic compounds [ 40 ], we expected that the PBL paste and sauce might have a hepatoprotective role through antioxidant activity. This antioxidant effect is similar to that of the paste and sauce extracts made of 30% (TMP30: 151.07%, 151.75%; TMS30: 148.69%, 151.37%), 50% (TMP50: 150.31%, 156.69%; TMS50: 150.63%, 151.27%), and 100% (TMP100: 152.11%, 158.30%; TMS100: 151.74%, 151.91%) TML [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…When the amino nitrogen level and relative protease activity was compared with pastes and sauces made of GM, it was found that the proteins were further fermented in the paste and sauce made with PBL50 and PBL100 than with GM. Furthermore, when the amino nitrogen level and relative protease activity were compared with the pastes and sauces made of 30% (TMP30: 0.369 mg/mL, 96.25%; TMS30: 2.967 mg/mL, 108.03%), 50% (TMP50: 0.408 mg/mL, 19.93%; TMS50: 3.255 mg/mL, 128.21%), and 100% (TMP100: 0.437 mg/mL, 142.6%; TMS100: 3.782 mg/mL, 13.53%) of TML [ 22 ], it was found that the proteins were further fermented in the paste and sauce made with PBL than with TML. These results are inferred, because PBL (57.86%) has a higher protein content than GM (40%) and TML (50.32%) [ 6 , 11 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very particular study is the one conducted by Hwang et al. (2019), in which the authors investigated the effects on ethanol‐damaged HepG2 cells of koji, a fermented oriental food obtained by growing the filamentous fungus Aspergillus oryzae on a cereal (rice or barley) or soy prepared from TML instead from usual substrates.…”
Section: Biological Effects Of Tm‐based Productsmentioning
confidence: 99%